Addressing Women’s Issues in Planning for Sustainable Development: A Comparative Study between Kurdish Women in Kurdistan Region of Iraq and Palestinian Women in the West Bank in Palestine - Dawwas, Dr. Emad Dawwas (Sulaimani Journal for Humanities, 2026)
The fifth goal of Sustainable Development Goals (SDGs) states that all discrimination against women and girls should be stopped as an essential requirement for sustainable future. Within the context of Kurdistan Region of Iraq (KRI) and the West Bank in Palestine (WBP), it might be early and difficult to talk about gender equality and put it in practice. However, women issues should be clearly stated in the plans and policy documents as one requirement to reach the fifth SDG. This study aims to analyze the extent to which women issues are considered in urban planning process - as one of the most effective tools of sustainable development- in two regions: Kurdish Region in Iraq (KRI) and the West Bank in Palestine (WBP). Referring to a number of urban planning documents from both regions, the analysis was conducted by contextual text analysis for all available planning documents with reference to the 17 SDGs. When comparing the results from KRI and WBP, it is obvious that there is high similarity in the level of interest in women's issues in both regions regarding equality and economic sustainability goals. On the other hand, the results show significant differences in the issues regarding the goals of basic services and the goals of sustainable built and natural environments.